Analisa Dampak Kompetensi Komunikasi Antar Budaya terhadap Empati Budaya : Studi Kasus Mahasiswa Perantau Etnis Madura - Indyana Ummi Aisyah; Nikmah Suryandari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study analyzes the relationship between intercultural communication competence and cultural empathy in Madura ethnic nomadic students. As a group that often faces challenges in cross-cultural communication, migrant students need to have high adaptability in order to interact effectively in diverse academic and social environments. This study aims to understand how the process of cross-cultural communication can shape the cultural empathy of Madura ethnic nomadic students, as well as how factors such as cross-cultural awareness, ease of perspective, feelings of empathy, and expressions of empathy contribute to their adaptation. This study uses a qualitative approach with an in-depth interview method of Madurese ethnic nomadic students spread across several provinces in Indonesia. The results of the study show that effective cross-cultural communication can help students in adjusting to a new environment, increasing comfort in interacting, and strengthening cultural empathy. Key factors contributing to this process include the ability to understand cultural differences, language skills, as well as a willingness to participate in the local culture.